2004
DOI: 10.1155/s0161171204305284
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Partial sums of functions of bounded turning

Abstract: We determine conditions under which the partial sums of the Libera integral operator of functions of bounded turning are also of bounded turning

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 4 publications
(2 reference statements)
0
11
0
Order By: Relevance
“…The number 3 8 is sharp ( [13]). In [14], it was also shown that the partial sums of the Libera integral operator of functions of bounded turning are also of bounded turning. We determine conditions under which the partial sums (5-7) of the multiplier integral operators (2-4) of analytic univalent functions of bounded turning are also of bounded turning.…”
Section: Introductionmentioning
confidence: 99%
“…The number 3 8 is sharp ( [13]). In [14], it was also shown that the partial sums of the Libera integral operator of functions of bounded turning are also of bounded turning. We determine conditions under which the partial sums (5-7) of the multiplier integral operators (2-4) of analytic univalent functions of bounded turning are also of bounded turning.…”
Section: Introductionmentioning
confidence: 99%
“…In [1], Babalola defined a new concept of quasi-partial sums of the generalized Bernardi integral operator for analytic univalent functions and he extended an earlier result of Jahangiri and Farahmand [5]. Yet analogous results on harmonic univalent functions have not been so far explored.…”
Section: Introductionmentioning
confidence: 99%
“…Denote by A the class of functions: f (z) = z + a 2 z 2 + · · · (1.1) which are analytic in the unit disk E = {z : |z| < 1}. In [5] Jahangiri and Farahmand studied the partial sums of the Liberal integral of the class B(β), which consists of functions in A satisfying Re f ′ (z) > β, 0 ≤ β < 1. Functions in B(β) are called functions of bounded turning.…”
Section: Introductionmentioning
confidence: 99%
“…The result of Jahangiri and Farahmand [5] naturally leads to inquistion about a more general class of functions (including B(β) as a special case), which was introduced in [7] by Opoola, and has been studied extensively in [2]. This is the class T α n (β) consisting of functions f ∈ A which satisfy the inequality:…”
Section: Introductionmentioning
confidence: 99%